Pembuatan Nano Kitosan dengan Metode Gelasi Ionik Menggunakan SEM (Scanning Elektron Microscopy) - Pratiwi One; Astin Lukum; La Alio; Erni Mohamad; Kostiawan Sukamto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine how nano chitosan is produced through the ionic gelation method. The process of making nano chitosan is carried out using variations in chitosan concentrations of 1%, 5%, and 10%, and using a magnetic stirrer. Morphological tests were carried out using Scanning Electron Microscopy (SEM) to observe the shape and size of the particles formed. The addition of TPP (Trisodium Tripolyphosphate) as a crosslinker and certain surfactants are used to increase particle stability. Treatment for ±2 hours showed optimal results in terms of a more homogeneous particle size distribution. Based on the results of SEM observations, it is known that increasing the concentration and time settings and the use of appropriate surfactants can reduce wrinkles in nano chitosan particles. The particle size obtained is in the range of 278–350 nm. Thus, the ionic gelation method has proven effective in producing uniform nano chitosan and has good morphology for further applications.